A National Survey of Neonatologists: Barriers and Prerequisites to Introduce Point-of-Care Ultrasound in Neonatal ICUs. Issue 4 (December 2017) - Mirza, Hussnain S.; Logsdon, Gregory; Pulickal, Anoop; Stephens, Mark; Wadhawan, Rajan
Abstract : Abstract: Point-of-care (POC) ultrasound refers to the use of portable imaging. Although POC ultrasound is widely available to the neonatologists in Australia and Europe, neonatologists in the United States report limited availability. Our objective was to seek the US neonatologists' perception of barriers and prerequisites in adopting POC ultrasound in neonatal intensive care units. An online survey link was sent via e-mail to 3000 neonatologists included in the database maintained by the American Academy of Pediatrics. Survey results (n = 574) were reported as percentage of total responses. Personal experience requiring an urgent sonography in managing cardiac tamponade or pleural effusion was reported by 78% respondents. However, emergent ultrasound (⩽10 min) was not available in 80% of the neonatal intensive care units. We compared the responses based on years of clinical experience (>20 vs <20 years), with 272 (48%) neonatologist reporting more than 20 years of experience. Similarly, results from neonatal fellowship programs were compared with nonteaching/teaching hospitals, with 288 (50%) replies from neonatology fellowship programs. Compared with senior neonatologists, respondents with less than 20 years of clinical experience consider POC ultrasound enhances safety and accuracy of clinical procedures (87% vs 82%) and favor adopting POC ultrasound in clinical practice (92% vs 84%). There were no differences in opinion from neonatology fellowship programs compared with the nonteaching/teaching hospitals. Lack of training guidelines, inadequate support from local radiology department, and legal concerns were reported as the top 3 primary barriers in adopting POC ultrasound. If these barriers could be resolved, 89% respondents were inclined to adopt POC ultrasound in clinical practice.